ANALISIS SEMIOTIKA FILM MY STUPID BOSS - Rhicard Yulio Resmardi; Dian Esti Nurati, Siswanta (Solidaritas, 2017)
ANALISIS SEMIOTIKA FILM MY STUPID BOSS Oleh:Rhicard Yulio ResmardiDian Esti NuratiSiswanta ABSTRACT This research was the excavation of the meaning of the message contained in a few selected scene in the movie